Penyuluhan dan Pemberdayaan Kader Tentang Penyakit Kecacingan di Desa Bone Kecamatan Nekamese Kabupaten Kupang - Meliance Bria; Murry Jermias Kale; Ni Made Susilawati (Institut Nalanda, 2023)
Worms are a health problem that is still widely found. Worms caused by several intestinal worms transmitted through the soil are called Soil Transmitted Helminths (STH). Elementary school children are an age group that is susceptible to infection with worms. Worm infections can have a serious impact if not treated with deworming medication and a clean and healthy lifestyle of the person. This community service is carried out to be an outreach to improve and empower the community, especially elementary schools, about clean living behavior in dealing with worms. Behaviors such as hand washing habits, nail hygiene, footwear habits, bowel habits and to determine environmental sanitation risk factors such as latrine ownership, availability of clean water, and ownership of trash bins related to stunting in children’s parents Bone Village, Nekamese District. The number of children is 28 people. Counseling and empowerment of cadres about worms in Bone Village, Nekamese District, Kupang Regency has been carried out well involving the children's parents. The evaluation showed a good increase in understanding about worms from cadres, children and parents.